Regulation Of Sharia Microfinance Institutions Toward Credit Cooperations Based On Sharia Principles - Martania, Mira; Islahudin, Ahmad Noor; Kurniati, Herlina (Universitas Islam Negeri Raden Intan Lampung, 2023)
In empowering the people's economy through providing inclusive and sharia-based financial access. Islamic microfinance institutions, namely credit cooperatives, which aim to provide financial services in accordance with sharia principles to their members. One of the theories underlying the regulation of Islamic microfinance institutions towards credit cooperatives based on Islamic principles is that Islamic finance must follow Islamic principles in every aspect of its operations, including the prohibition of usury, gharar, and maysir, as well as an emphasis on fairness, sustainability, and economic empowerment. The problem of different understanding and interpretation of sharia principles is a challenge in the implementation of this law. In addition, compliance with and supervision of sharia principles is also a problem because it requires deep understanding and effective oversight mechanisms. The purpose of the regulation of Islamic microfinance institutions for credit cooperatives based on sharia principles is to create financial institutions that can provide financial services in accordance with sharia principles to their members. This includes empowering the people's economy, creating a fair and sustainable financial system, and providing more inclusive financial alternatives for the community.Keywords: Economic empowerment, sharia principles, compliance, supervision, regulation